Leadership Style and Nurse Performance in the Inpatient Ward of Muhammadiyah Gresik Hospital: A Cross-sectional Study - Sholichah, Farchatus; Widiharti, Widiharti; Sari, Diah Jerita Eka (Universitas Airlangga, 2023)
Introduction: Nurses responsible to perform optimally, adhere to the standards set by the hospital to gain high quality of nursing care. The determining factor for the quality of nursing services is the performance. Leadership style of the head ward is one of the factors that influence the performance of nurses. The aim of this study is to analyze the relationship between the leadership style and the performance of nurses in the inpatient ward at Muhammadiyah Gresik Hospital. Method: The research design is correlational with a cross-sectional approach. The sampling technique in this study was total sampling with a total sample of 44 nurses. Data collection for leadership style using a questionnaire, while the nurse performance using a performance appraisal checklist. The statistical test in this study used the Rank Spearman test to determine the correlation between variables. Results: Most of the leadership style in the inpatient ward of the Muhammadiyah Gresik Hospital is a democratic leadership style (79.5%), most of the nurses have performance at the sufficient category (65.9%). There is a relationship between the leadership style of the head of the ward and the performance of nurses in the inpatient ward at Muhammadiyah Gresik Hospital (p=0,000). Conclusions: The democratic leadership style has a good influence on the nurse performance. Further study for improving nurse performance by optimizing leadership role is needed.